(untitled) (Third Sector Social Economic Review, 2019)
In this study, the relationship between Participation-30 Islamic stock index and consumer confidence index, which represents investor sentiment, for the period of January 2011 - August 2018 was investigated in Turkey. During the analysis, Hatemi J - Irandoust (2012) hidden cointegration test and Hatemi J (2012) asymmetric causality tests, which take into account the structure of financial markets where different responses were given to positive and negative shocks due to the heterogeneous structure of the investors, were used. According to the results, there was no causality relationship between the Participation-30 index and the consumer confidence index. In addition, according to the result of cointegration analysis, the mentioned indices, in the case of positive shocks, have an integrated structure in the long term.